Effects of extrusion process, type and content of clays, and foaming process on the clay exfoliation in HMS PP composites - Laguna-Gutierrez, Ester; Van Hooghten, Rob; Moldenaers, Paula; Angel Rodriguez-Perez, Miguel (Journal of applied polymer science, 2015)
ABSTRACT The use of a high melt strength polypropylene (HMS PP) matrix reinforced with layered clays could be very useful to improve the properties of materials produced with processes involving melt stretching, like foaming. The control of the particles structure, that is, the degree of exfoliation and the clay distribution in the polymeric matrix, is the key to achieve the desired properties. In this study, the effects of the extrusion process, the clay type and content, and the foaming process on the morphology of different HMS PP based composites are studied. Both, natural and organomodified clays were used. The extrusion process has a negative effect in the composites containing natural clays as their interlayer distance decreases as the number of extrusion cycles increases. On the contrary, this process improves the intercalation of the organomodified clays. However, in both composites the interlayer spacing decreases when the clay content increases. While a percolated network is formed in the composites containing organomodified clays, no network is formed with the natural clays. Finally, the effect of the foaming process has also been analyzed. The Improved Compression Moulding (ICM) route was used to produce the foamed materials. This technique subjects the materials only to a temperature and a pressure gradient without applying any other external forces that could contribute to the clay exfoliation. In this way, only the effects of foaming and melt stretching are observed. In both composites, an increase in the interlayer distance is observed when the materials are foamed. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42828.